2008
DOI: 10.1111/j.1475-4983.2008.00810.x
|View full text |Cite
|
Sign up to set email alerts
|

Early Ordovician Conodonts From Tarutao Island, Southern Peninsular Thailand

Abstract: Early Ordovician conodont faunas of the Thung Song Formation on Tarutao Island, southern peninsular Thailand, consist of 14 known species belonging to 17 genera, and eight undescribed species. Utahconus tarutaoensis and Filodontus tenuis are new species. Three conodont zones: the Rossodus manitouensis Zone, the Utahconus tarutaoensis Zone and the Filodontus tenuis Zone, in ascending order, are defined in the study sections. These are coeval with the interval from the Rossodus manitouensis Zone to the Acodus de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…The relatively deep water Upper Ordovician Pa Kae Formation in Satun province, Thailand shares multiple trilobite genera (including 4 species) and facies in common with the Pagoda Limestone of the South China Block (Fortey, 1997;Zhou et al, 2016). Studies of conodont faunas from Satun and northern Malaysia show a coincident shift from shelf assemblages in the Early and Middle Ordovician to deeper water forms (Agematsu et al, 2007(Agematsu et al, , 2008, consistent with the trilobite data (Fortey, 1997). Burrett et al (2016) suggested that faunal links to South China increased in association with Late Ordovician sea level rise, and they noted that there may be some regional biofacies differences within Sibumasu itself (see below).…”
Section: Sibumasu Precursor Relationships Of the Shan-thai Area To The Gondwanan Marginmentioning
confidence: 60%
See 1 more Smart Citation
“…The relatively deep water Upper Ordovician Pa Kae Formation in Satun province, Thailand shares multiple trilobite genera (including 4 species) and facies in common with the Pagoda Limestone of the South China Block (Fortey, 1997;Zhou et al, 2016). Studies of conodont faunas from Satun and northern Malaysia show a coincident shift from shelf assemblages in the Early and Middle Ordovician to deeper water forms (Agematsu et al, 2007(Agematsu et al, , 2008, consistent with the trilobite data (Fortey, 1997). Burrett et al (2016) suggested that faunal links to South China increased in association with Late Ordovician sea level rise, and they noted that there may be some regional biofacies differences within Sibumasu itself (see below).…”
Section: Sibumasu Precursor Relationships Of the Shan-thai Area To The Gondwanan Marginmentioning
confidence: 60%
“…8). Compared to that succession, the limestone facies may be slightly younger in the Canning Basin, as indicated by conodont fauna (Agematsu et al, 2008;Normore et al, 2018), possibly reflecting a transgressive succession in which Ko Tarutao was located somewhat further offshore. Comparable sandstone facies are also found in Bhutan, although the part of the Bhutanese succession that has been precisely dated is slightly older stratigraphically (Hughes et al, 2011;Greenwood et al, 2016) than the dated Sibumasu Cambrian succession.…”
Section: Sibumasu Precursor Relationships Of the Shan-thai Area To The Gondwanan Marginmentioning
confidence: 99%
“…Identical observations can be made for the material described as U. longipinnatus by Agematsu et al . (, p. 1450, pl. 1, figs ).…”
Section: Systematic Palaeontologymentioning
confidence: 99%
“…Recent work in the relatively thick Ordovician carbonate successions in Thailand and Malaysia by Agematsu et al . (,b) has led to the discovery of notable conodont faunas. Whereas those of Tremadocian and slightly younger age are of North American type, the Sandbian–Katian faunas are dominated by taxa best known from Baltoscandia.…”
Section: The Modern Periodmentioning
confidence: 99%